Eksplorasi Sejarah Film Melalui Media Kreatif - RR Ella Evrita H, S. E, M.M, RR Ella Evrita H, S. E, M.M (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2024)
The purpose of this study is to examine the role of creative media, especially films, in perpetuating and creating history. Creative media can not only reflect social, political, and cultural conditions at the same time, but can also influence existing perceptions of history itself. This study explores qualitative methods of content analysis based on historical representations in films. The main focus of this research is film as a creative medium that simultaneously shapes historical narratives. Through innovative film techniques, emotional impact, and the empowerment of historical figures, films can influence the film industry and people's perception of history. An in-depth analysis of films such as Citizen Kane, Schindler's List, and Apocalypse Now shows how films can act as recorders and creators of history, shaping national and cultural identities and offering unique film techniques and styles. historical events. The study highlights the importance of criticism and a deep understanding of history in evaluating film performance and how creative media can stimulate critical thinking and social dialogue about history.